A Force to Be Reckoned With: College Women's Experiences With the #MeToo Movement. Issue 3 (9th October 2020) - Callender, Karisse A.; Klassen, Samantha
Abstract : The hashtag #MeToo was created for use on social media platforms to allow survivors of sexual violence to share their experiences. Our study describes a phenomenological analysis of college women's experiences with the #MeToo movement and its impact on their help‐seeking behaviors. Participants had varied reactions to the movement and experiences with help‐seeking, but broadly experienced the movement as a positive force in society. Implications for college counselors and recommendations for future research are provided.